Design of Back-to-Back Converter Interface for Electric Spring in a Distribution System - Deepika, K. K.; Kumar, J. Vijaya; Pinni, Srinivasa Varma; Sura, Srinivasa Rao; Sankar, R. S. Ravi (Frontiers in Energy Research, 2022)
In distribution system, erratic output power of distributed generation causes fluctuations in the available power to critical loads on demand side. A novel electric spring with back to back converter configuration is proposed. Besides PCC voltage regulation and power control, proposed converter integrates ES to Grid without compromising the DC link voltage and quality of grid current. It comprises an instantaneous DC link voltage control, active power control, PCC voltage control and a hysteresis band current control. Systematic design of the parameters in the configuration are detailed. Simulations were performed in MATLAB/Simulink and series of comparative analysis at various control stages were demonstrated. Quality of grid current was analyzed with PI, PR and Hysteresis band current controllers. It was established that Hysteresis band current controller gave best performance. Similarly, DC link voltage was efficiently regulated with instantaneous DC link voltage controller than the conventional controller.